2011
DOI: 10.1108/19852511111173103
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the board structure on earnings management: evidence from Portugal

Abstract: Purpose -This study aims to extend previous research by examining empirically how board structure affects the magnitude of earnings management for companies listed in Portugal. In particular, the paper focuses on the main characteristics of the board structure that are highlighted by the Portuguese Securities Market Supervisory Authority recommendations, i.e. board size, board composition and board's monitoring committees. Design/methodology/approach -The OLS regression model is used to examine the effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 63 publications
5
12
1
6
Order By: Relevance
“…Concerning control variables, the result shows that a larger board size results in greater financial stability, which agrees with Geraldes- Alves (2011), who observed that boards with more directors are related to improved or goodquality reporting measured by the EM proxy. The results also show that financial stability is greater in firms with more concentrated ownership.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Concerning control variables, the result shows that a larger board size results in greater financial stability, which agrees with Geraldes- Alves (2011), who observed that boards with more directors are related to improved or goodquality reporting measured by the EM proxy. The results also show that financial stability is greater in firms with more concentrated ownership.…”
Section: Resultssupporting
confidence: 86%
“…The results also show that financial stability is greater in firms with more concentrated ownership. Geraldes- Alves (2011) and Alves (2012) discovered a similar result with the reporting quality, measured by EM. The findings suggest that firms with a large ROA ratio are more likely to be financially stable, as are firms in the manufacturing sector.…”
Section: Resultssupporting
confidence: 59%
“…This result leads to validate the H1 hypothesis. Moreover, this result is consistent with that of Gonzalez andGarcia-Meca (2013), Alexander andPaquerot, (2011) and Alves (2012).…”
Section: Testing Panel Datasupporting
confidence: 82%
“…(Ahmed Sheikh et al , 2013). Geraldes Alves (2011) predicted a non-linear relationship between board size and earnings management. Kumar and Singh (2013) found a negative relationship between board size and firm value in the Indian context.…”
Section: Literature Reviewmentioning
confidence: 99%